Inovasi Pendidikan Anti Korupsi Dalam Membangun Masyarakat Yang Berintegritas - Dewi Maharani; M. Akbar Adjiguna Bmy; Paten Nuri; Nopal Gustin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Innovation in anti-corruption education is crucial in efforts to form a society with integrity. This article explores various innovative strategies in education that aim to reduce levels of corruption and strengthen the values ​​of integrity in society. An inclusive approach through an integrated curriculum with character education, training for teachers and teaching staff, as well as the use of information technology as an interactive learning tool is the main focus. Data analysis and case studies support the effectiveness of these innovative measures in stimulating awareness, building skills and shaping attitudes against corruption. Thus, innovation in anti-corruption education is not only about transferring knowledge, but also about forming mindsets and behavior that are rooted in society, making it a strong foundation for building a society with integrity.